2022
DOI: 10.1136/bjophthalmol-2022-321145
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with glaucoma-specific quality of life in a US glaucoma clinic in a pilot implementation of an online computerised adaptive test (GlauCAT)

Abstract: ObjectivesMeasure quality of life (QoL) outcomes using a novel computerised adaptive test in a clinical setting, and determine the social and demographic factors associated with specific QoL domains in patients with glaucoma.DesignCross-sectional study between July 2020 and April 2021.ParticipantsEnglish-speaking adults presenting to glaucoma clinic. Patients with cognitive impairment on a six-item cognitive impairment screen or with intraocular surgery within 90 days prior to presentation were excluded.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Indeed, using our online CAT testing platform (PROMinsight), six QoL domains of GlauCAT™-Western (taking 8 min on average) were recently administered to > 200 glaucoma patients while waiting to see their treating doctor at Mass. Eye and Ear Institute, with the HRQoL scores discussed during the patients’ consultations [ 18 , 48 ]. Analysis of the group data found that VA was associated with greater activity limitation and worse mobility, while poorer VF mean deviation was associated with worse emotional well-being.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, using our online CAT testing platform (PROMinsight), six QoL domains of GlauCAT™-Western (taking 8 min on average) were recently administered to > 200 glaucoma patients while waiting to see their treating doctor at Mass. Eye and Ear Institute, with the HRQoL scores discussed during the patients’ consultations [ 18 , 48 ]. Analysis of the group data found that VA was associated with greater activity limitation and worse mobility, while poorer VF mean deviation was associated with worse emotional well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the group data found that VA was associated with greater activity limitation and worse mobility, while poorer VF mean deviation was associated with worse emotional well-being. These pilot results provide real-world evidence of the implementation feasibility of GlauCAT™ in routine clinical care enabling real-time discussion of results [ 49 ] and subsequent analysis of group data to better understand the factors associated with HRQoL outcomes in glaucoma patients [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In view of the current push toward value-based clinical care, 9 we have developed an online CAT testing platform (PROMinsight) using Concerto open-source software that can be implemented on any smart device, enabling real-time scoring and reporting of data. 41 Indeed, a pilot study conducted in glaucoma clinics at Massachusetts Eye and Ear Institute, where 216 glaucoma patients completed six GlauCAT tests on a tablet device while waiting to see their treating doctor, 42 , 43 showed that patients took just 8 minutes and 5 seconds (median) to complete all six GlauCAT tests, 43 providing real-world evidence of the feasibility of implementing GlauCAT in routine clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…Compromised QoL scores with both GQL-15 and VFQ-UI were reported in glaucoma subjects with a wide range of visual function impairment compared with normal subjects. 13,14 Studies have investigated the relationship between BVF loss and only vision-specific QoL in glaucoma [15][16][17] and stated that the impact of IVF mean deviation (MD) on visionspecific QoL was similar to that of the better eye MD values. 4,18 In conjunction, individuals with unilateral VF loss reported better QoL than individuals with bilateral glaucoma.…”
mentioning
confidence: 99%
“…20 In view of the hemifield BVF loss, inferior VFD is reported to majorly influence daily life activities compared with superior VFD. 21,22 Previously reported studies have investigated the impact of glaucomatous functional vision loss on QoL among glaucoma subjects with central vision impairment [13][14][15][16][17][18][19][20][21][22] and concluded that the central visual acuity (VA) is the most influential factor on QoL than the presence and severity of VFD. 22 This highlights the need for evaluating the VRQoL among glaucoma subjects with spared central VA. A comprehensive VRQoL assessment using vision-specific and disease-specific tools among Indian subjects diagnosed with glaucomatous field loss, but with spared central acuity, is not reported.…”
mentioning
confidence: 99%